Birth and emergency preparedness and associated factors among postnatal mothers at Base Hospital Balangoda, Sri Lanka - Perera, Nadeeka; Goonewardena, Sampatha E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Birth and emergency preparedness is a cost effective and evidence based intervention recommended by the current WHO maternal care model and used in maternal care package in Sri Lanka. The aim of the study was to describe the birth and emergency preparedness and its associated factors among postnatal mothers at Base Hospital, Balangoda, Sri Lanka. Methods: A descriptive cross sectional study was conducted among 427 postnatal mothers delivered after completion of 37 weeks of period of amenorrhoea. Participants were recruited by systematic sampling. Data was collected using a pre tested interviewer administered questionnaire. Data was analysed using SPSS version 21. Descriptive statistics and multiple logistic regression analysis were done to calculate the adjusted Odds ratio and 95% confidence interval. A probability of p<0.05 was considered significant. Results: Majority 84.3% (n=338) had registered at antenatal care before 12 weeks and 89.3% (n=358) had received domiciliary care during antenatal period. Majority of the mothers (59.4%,n=238) were well prepared for birth and emergencies. Univariate analysis showed a significant association with well preparedness were ethnicity (p<0.001), religion (p<0.001), married mothers in union (p<0.05), higher educational qualifications by both partners (p<0.01), receiving adequate maternity social support (p<0.001), received domiciliary care by PHM (p<0.05) and participation at antenatal classes by mother (p<0.05). After adjusting for confounders, attained higher educational qualifications by mother (OR=1.89, 95% CI=1.27-2.93) and having received social support (OR=2.64, 95% CI=1.43-4.87) were significant factors associated with birth preparedness. Conclusions: The overall preparedness for birth and emergencies was satisfactory. Modifiable significant associated factors need due attention.